2014
DOI: 10.1002/bdm.1818
|View full text |Cite
|
Sign up to set email alerts
|

Are People Naïve Probability Theorists? A Further Examination of the Probability Theory + Variation Model

Abstract: Two experiments tested predictions derived from the Probability Theory + Variation (PTV) model. PTV model assumes that judgments follow probability theory, but systematic errors arise from noise in the judgments. Experiment 1 compared the PTV model to a configural weighted averaging model in joint probability judgment and found more support for the PTV model in diagnostic cases. Specifically, noise was negatively correlated with semantic coherence and conjunction and disjunction fallacies increased when order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 31 publications
5
19
0
Order By: Relevance
“…Our model, however, resolves this conflict. As we saw above, our model predicts an average value of 0 for the addition form of Bayes' rule, just as observed by Fisher and Wolfe (2014). Our model also predicts that, on average, the difference between the conjunction ratio and people's conditional probability estimates will be positive.…”
Section: Previous Results On Conditional Probability Estimationsupporting
confidence: 79%
See 2 more Smart Citations
“…Our model, however, resolves this conflict. As we saw above, our model predicts an average value of 0 for the addition form of Bayes' rule, just as observed by Fisher and Wolfe (2014). Our model also predicts that, on average, the difference between the conjunction ratio and people's conditional probability estimates will be positive.…”
Section: Previous Results On Conditional Probability Estimationsupporting
confidence: 79%
“…The same result holds for the second identity. A number of experiments have shown that these identities do in fact hold in people's probability judgments, just as predicted by the model: when we ask people to estimate probabilities for the terms in these identities for a range of events, and then combine each person's estimates according to the identity, the values obtained are distributed approximately symmetrically around the 0 value required by probability theory, just as predicted by our model (Costello and Watts, 2014, Costello and Mathison, 2014, Fisher and Wolfe, 2014.…”
Section: Our Model Of Probability Estimationmentioning
confidence: 52%
See 1 more Smart Citation
“…Our model thus predicts that this expression will have a value of 0, on average, in people's probability judgments just as required by standard probability theory. Exactly this pattern of agreement is seen in experimental results (Costello & Mathison, ; Costello & Watts, , , ; Fisher & Wolfe, ).…”
Section: The Probability Theory Plus Noise Modelsupporting
confidence: 81%
“…In an experiment asking participants to estimate the probability of a range of future events (such as a future increase in cigarette taxes and a future decline in smoking rates) and of various conjunctions and disjunctions of those events, we found that people's probability estimates gave values for the addition law that were, on average, very close to 0 as required by probability theory; similar results held for a number of other such ‘cancelling’ expressions (Costello & Watts, ). Finally, in an experiment where participants were given personality descriptions for a range of imaginary people and then asked to assess the probability of various direct, conjunctive, disjunctive and conditional statements being true for those people, Fisher and Wolfe () found that people's probability estimates gave a value for the addition law that was, again, very close to 0 as required by probability theory. Together, these results suggest that our model applies to probability estimation for events in general and is not limited solely to events that have previously been seen.…”
Section: Discussionmentioning
confidence: 99%